2008
DOI: 10.3791/837
|View full text |Cite
|
Sign up to set email alerts
|

Paradigms for Pharmacological Characterization of C. elegans Synaptic Transmission Mutants

Abstract: The nematode, Caenorhabditis elegans, has become an expedient model for studying neurotransmission. C. elegans is unique among animal models, as the anatomy and connectivity of its nervous system has been determined from electron micrographs and refined by pharmacological assays. In this video, we describe how two complementary neural stimulants, an acetylcholinesterase inhibitor, called aldicarb, and a gamma-aminobutyric acid (GABA) receptor antagonist, called pentylenetetrazole (PTZ), may be employed to spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 2 publications
4
30
0
Order By: Relevance
“…unc-4 ( e120 ) mutants are defective in cholinergic signaling due to mutations in the UNC-4 homeodomain protein that is required for cholinergic DA and VA motor neuron development (Esmaeili et al, 2002; Miller et al, 1992). In contrast, 100% of the unc-25 ( e156 ) mutants, which are defective in the GABA synthesis enzyme glutamic acid decarboxylase (GAD), and snb-1 ( md247 ) mutants, which are defective in general synaptic transmission, show robust anterior convulsions after 30 min of PTZ exposure, as has been previously reported (Locke et al, 2006, 2008). Interestingly, we found that nearly 50% of emb-27 ( g48 ) CDC16 mutant animals exhibit anterior convulsions after 30 min of PTZ exposure and more than 90% of emb-27 ( g48 ) CDC16 animals and 40% of emb-30 ( g53 ) APC4 animals were convulsing after 60 min of PTZ exposure (Fig.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…unc-4 ( e120 ) mutants are defective in cholinergic signaling due to mutations in the UNC-4 homeodomain protein that is required for cholinergic DA and VA motor neuron development (Esmaeili et al, 2002; Miller et al, 1992). In contrast, 100% of the unc-25 ( e156 ) mutants, which are defective in the GABA synthesis enzyme glutamic acid decarboxylase (GAD), and snb-1 ( md247 ) mutants, which are defective in general synaptic transmission, show robust anterior convulsions after 30 min of PTZ exposure, as has been previously reported (Locke et al, 2006, 2008). Interestingly, we found that nearly 50% of emb-27 ( g48 ) CDC16 mutant animals exhibit anterior convulsions after 30 min of PTZ exposure and more than 90% of emb-27 ( g48 ) CDC16 animals and 40% of emb-30 ( g53 ) APC4 animals were convulsing after 60 min of PTZ exposure (Fig.…”
Section: Resultssupporting
confidence: 59%
“…In C. elegans , PTZ induces seizure-like convulsions in animals with defects in GABA neurotransmission. Wild type animals and those with defects only in cholinergic signaling do not exhibit PTZ-induced convulsions (Locke et al, 2006, 2008; Williams et al, 2004). It should be noted, however, that the precise mechanism of action of PTZ in C. elegans is not completely clear and cannot only be explained by PTZ acting as a GABA signaling antagonist because GABA signaling mutants alone do not exhibit spontaneous seizures and the effects of PTZ on convulsions in C. elegans are only apparent when GABA transmission is also reduced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral and pharmacological assays: Convulsion assays were performed, as previously described (Williams et al 2004;Locke et al 2008). Concentrations of PTZ (Sigma) employed are indicated in the text.…”
Section: Methodsmentioning
confidence: 99%